Terahertz Metamaterials: Electrical Control of Electromagnetically Induced Transparency by Terahertz Metamaterial Funneling (Advanced Optical Materials 2/2019). Issue 2 (18th January 2019) - Jung, Hyunseung; Jo, Hyunwoo; Lee, Wonwoo; Kim, Beom; Choi, Hyunyong; Kang, Moon Sung; Lee, Hojin
Abstract : In article number1801205, Hojin Lee and co‐workers demonstrate an active electromagnetically induced transparency (EIT) surface based on a metamaterial array covered with ionic gel. Each "H" shape meta‐atom is connected through the patterned graphene lines, of which the variable conductivity determines the active EIT behavior and corresponding group delays of the terahertz wave. The cover page displays electrically controllable funneling of terahertz waves in the ionic‐gel‐coated graphene meta‐atoms for realizing active EIT spectra.